Niewydolność serca i płuc, transplantologiaInfections after heart transplantation - Sioła, Mirosława (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Infections, apart from acute rejection and circulation complications, are among the most frequent complications after heart transplantation. This paper presents risk factors that lead to infections besides immunosuppression and the aetiological factors that cause infections in heart recipients. This paper also sums up the results of microbiological examination of patients operated on in the Silesian Centre for Heart Disease in Zabrze.